Frequency of mutation, lethality and efficiency of ethyl methane sulphonate and sodium azide on foxtail millet (Setaria italica [L.] P. Beauv.) - Esson, A. E.; Adebola, M. I.; Yisa, A. G. (Journal of Scientific Agriculture, 2018)
This study was carried out to determine the frequency of lethality, Mutagenic frequency, effectiveness and efficiency induced by ethyl methane sulphonate (EMS) and sodium azide on foxtail millet. The seeds were treated with different concentrations of EMS and sodium azide. Number of morphological mutant were observed visually and recorded. Mutagenic frequency, effectiveness and efficiency were highest for EMS at 0.1% concentration (Mutagenic frequency 7.50% effectiveness 18.75% and efficiency 7.50%) and sodium azide at 0.2% concentration (Mutagenic frequency 7.00%, effectiveness 1.84% and efficiency 1%). Lower concentrations of EMS and sodium azide were more effective and efficient in inducing mutation with low biological damages and high mutation frequency. EMS was more effective and efficient in inducing variability in foxtail millet than sodium azide. Therefore, mutants foxtail millet with low biological damages and high mutation frequency can be developed at low concentration of EMS and sodium azide for breeding of foxtail millet.